Detection of Salmonella enterica serovar Typhi by nested PCR using different procedures of nucleic acid extraction - Islam, Md. Jahedul (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2010